Transformasi Tari Bedana Tradisi Menjadi Tari Bedana Kreasi - Riyan Hidayatullah; Indra Bulan (Universitas Lampung, 2017)
Bedana Dance is one of traditional arts masysrakat Lampung. This dance was brought by the Arabs in about 1930 who later taught to three children named Ma'ruf, Amang, and Abdullah. They then spread this dance to all corners of Lampung. Bedana Dance is a traditional dance that has its roots and is perceived as a symbol of a very wide tradition about the view of life as well as a friendly and open environment environment. Along with the growing time and understanding of the society will be dance bedana, so presently it is assumed the bedana dance has undergone a fairly strong transformation. Traditional Dance of Dance has evolved into dance bedana creations. There is a change in the formation of dancers who are group, in addition to the dance of the bedana has also been danced in traditional events and other entertainment events. In this study, descriptive method is used to find and describe the form of motion danana dance and the meaning of motion dance traditional dress become creations. This new dance is famous for the term new dance creations. Similarly with Bedana Dance, where the dance was originally a traditional dance, but as many developed so that the models and equipment used in dance bedana also experienced a changeKeywords: Dance of creations creations, dance transformation, Lampung DOI: http://dx.doi.org/10.23960/aksara/v18i2.pp178-191